Perbuatan Melawan Hukum Yang Dilakukan Pengembang PT. Hadez Graha Utama Terhadap Konsumen Pada Perjanjian Jual Beli Perumahan Dalam Putusan Putusan Nomor 395/Pdt.G/2021/Pn.Bks - Setyawan, Muhammad Agung; Agus, Dede; Anwar , Jarkasi (Indonesian Journal Publisher, 2025)
This study aims to analyze the form of unlawful acts in housing sale and purchase agreements and their legal consequences for consumers and developers, with a case study of Decision Number 395/Pdt.G/2021/Pn.Bks involving PT. Hadez Graha Utama. The research method uses a normative legal approach by analyzing secondary data in the form of laws and regulations, court decisions, and relevant legal literature. This study examines the legal aspects of consumer protection and contract law in the context of housing property sales and purchases. The results of the study indicate that the developer has committed an unlawful act by starting construction without having a Building Construction Permit (IMB). The court decided that the developer must pay compensation of IDR 192,730,800.00 to consumers along with court costs. This decision is an important precedent in providing legal protection for housing consumers. The conclusion of this study shows that the court decision provides legal certainty and protection for consumers, as well as a warning for developers to comply with legal provisions in housing development. Further research is needed to examine the implementation of similar decisions and their impact on the property industry and consumer protection in Indonesia.